Pembinaan dan Pengawasan Penyelenggaraan Pemerintahan Daerah Otonomi Khusus di Papua - Barik Muhammad Kurniawan Ardy (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
This study aims to analyze the performance of the Directorate of Regional Arrangement, Special Autonomy, and the Regional Autonomy Advisory Council in fostering and supervising the implementation of special autonomy in Papua, analyzing the supporting factors and obstacles to the performance of the guidance and supervision carried out by the directorate as well as analyzing the strategy of guidance and supervision in the administration of local government. Special autonomy in Papua. Descriptive qualitative research design through an inductive approach. Data obtained from observation, documentation, and interviews with key informants were then analyzed using triangulation to analyze supporting and inhibiting factors and strategies, used SWOT Matrix and Litmus Test. Based on the results of data analysis, it is concluded that; (1) the directorate's performance in fostering and supervising the administration of the particular autonomous regional government in Papua has not been optimal; (2) performance supporting factors. Namely, organizational legality, human resources, leadership commitment, inter-institutional linkages, national priorities and access to coordination communication as well as performance inhibiting factors, namely, limiting regulations, limited funding, differences in employee orientation, national disintegration, 'span' of control which is far away, and the commitment between stakeholders is not optimal and; (3) the strategy resulting from this research is the "K5" strategy, namely strengthening in terms of Institutional, Communication, Coordination, HR Quality, and IT Quality. From this conclusion, the researcher provides suggestions, namely restructuring the directorate, preparing guidance and supervision instruments in the implementation of Papua's special autonomy, expanding cooperation networks or partnerships with stakeholders, developing digital-based information systems, facilitating employees to attend training or workshops, and a commitment to realizing the "K5" strategy.